Current Ratio Dan Pertumbuhan Perusahaan Terhadap Kebijakan Dividen Pada JII Tahun 2020-2024 - Michael Jacksen; Ratna Juwita (MDP Student Conference, 2026)
This study aims to analyze the effect of the Current Ratio (CR) and firm growth (GTA) on dividend policy in companies included in the Jakarta Islamic Index (JII) during the 2020–2024 period. The study employs a quantitative approach using secondary data obtained from corporate financial statements published by the Indonesia Stock Exchange. The sampling technique used is purposive sampling, resulting in 80 research samples. The data analysis method applied is multiple linear regression analysis, with hypothesis testing conducted through t-tests (partial) and F-tests (simultaneous). The t-test results indicate that, partially, the Current Ratio (CR) has a negative and significant effect on dividend policy, with a t-value of −9.452 and a significance level of 0.000. Furthermore, firm growth (GTA) is also proven to have a negative and significant effect on dividend policy, with a t-value of −5.685 and a significance level of 0.000. The simultaneous test (F-test) shows that the Current Ratio (CR) and firm growth jointly have a significant effect on dividend policy, with an F-value of 65.228 and a significance level of 0.000. These findings indicate that liquidity levels and asset growth play an important role in determining dividend distribution policies in companies listed on the Jakarta Islamic Index.